A cross-sectional study on prevalence of chronic obstructive pulmonary disease (COPD) in India: rationale and methods - Rajkumar, Prabu (BMJ Open, 2017)
BACKGROUND: Chronic obstructive pulmonary disease (COPD) is a common preventable and treatable chronic respiratory disease, which affects 210 million people globally. Global and national guidelines exist for the management of COPD. Although evidence-based, they are inadequate to address the phenotypic and genotypic heterogeneity in India. Co-existence of other chronic respiratory diseases can adversely influence the prognosis of COPD. India has a huge burden of COPD with various risk factors and comorbid conditions. However, valid prevalence estimates employing spirometry as the diagnostic tool and data on important comorbid conditions are not available. This study protocol is designed to address this knowledge gap and eventually to build a database to undertake long-term cohort studies to describe the phenotypic and genotypic heterogeneity among COPD patients in India. OBJECTIVES: The primary objective is to estimate the prevalence of COPD among adults aged ≥25 years for each gender in India. The secondary objective is to identify the risk factors for COPD and important comorbid conditions such as asthma and post-tuberculosis sequelae. It is also proposed to validate the currently available definitions for COPD diagnosis in India. METHODS AND ANALYSIS: A cross-sectional study will be undertaken among the populations of sub-urban areas of Chennai and Shillong cities, which represent the Southern and Northeastern regions of India. We will collect data on sociodemographic variables, economic characteristics, risk factors of COPD and comorbidities. The Global Initiative for Obstructive Lung Disease (GOLD) and Global Initiative for Asthma (GINA) definitions will be used for the diagnosis of COPD and asthma. Data will be analysed for estimation of the prevalence of COPD, asthma and associated factors. ETHICS AND DISSEMINATION: This study proposal was approved by the respective institutional ethics committees of participating institutions. The results will be disseminated through publications in the peer-reviewed journals and a report will be submitted to the concerned public health authorities in India for developing appropriate research and management policies.